Implikasi Kebijakan Kampus Merdeka Belajar terhadap Manajemen Kurikulum dan Sistem Penilaian Pendidikan Menengah Serta Pendidikan Tinggi - Wiwi Uswatiyah; Neni Argaeni; Masruroh Masrurah; Dadang Suherman; Ujang Cepi Berlian (Jurnal Dirosah Islamiyah, 2021)
This policy of the Minister of Education and Culture deserves to be called a change that is quite extreme, this then raises some doubts in the minds of academics. Among the big questions that arise from the policy of independent Learning, Free Campus ”is 1. What is the definition of Government policy? 2. How is the concept of Free Learning? 3. What are the implications of the independent learning policy on curriculum management and assessment systems in secondary schools? 4. What are the implications of the policy of independent learning for curriculum management and assessment systems in higher education? This visionary policy of the Minister of Education and Culture deserves appreciation, however, several problems arise from the implementation of the policy of "Free Learning, Independent Campus" that must be resolved immediately. This paper attempts to review the form of the Freedom Learning policy and implementation challenges.